PENGARUH RETURN ON ASSETS, RETURN ON EQUITY, EARNING PER SHARE DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM - Ardiyanto, Agil; Wahdi, Nirsetyo; Santoso, Aprih (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
This study aims to determine the effect of Return On Assets, Return On Equity Earning Per Share, and Price to Book Value on Stock Prices. The population is the LQ-45 Index on the Indonesia Stock Exchange (IDX) for the 2014-2018 period.The study uses quantitative data with multiple linear regression techniques. The research sample was determined by purposive sampling technique and produced 14 company samples. Quantitative analysis, including: classic assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, model feasibility test through t test, F test and Coefficient of Determination.T test results show that only the Return On Equity, Earning Per Share, and Price to Book Value variables affect the Stock Price, while the Return On Asset variable has no effect on the Stock Price.